PENGARUH SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA RENTAL ASSA DI SURABAYA - Deysi Rosindah Tjakra; Siti Rahayu; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2018)
The research was purposed to know and analyze the preference of Service Quality (SERVQUAL) on Customer Satisfaction and Customer Loyalty in PT. Adi Sarana Armada tbk Surabaya. This study was conducted to further examine which dimensions have a major contribution to service quality. Data processing was conducted using SPSS 15 for windows and Amos Graphics 20. The sampling technique that used is non probability sampling with purposive sampling type. The samples that used in this research was 150 respondents, who qualify the specified characteristics of the population. The results of this study indicate the influence between 5 (five) dimensions of Service Quality variable to Variable Satisfaction and Loyalty Variables at PT. Adi Sarana Armada tbk Surabaya in doing car rental.